Analisis Komparatif Akad Muzara'ah dan Mukhabarah dalam Sistem Bagi Hasil Pertanian: Perspektif Hukum Islam - Farah Qalbia; M. Reza Saputra (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to analyze the comparison between Muzara'ah and Mukhabarah contracts in the agricultural profit-sharing system from the perspective of Islamic law. Both contracts represent forms of cooperation between landowners and cultivators aimed at increasing farm productivity and farmers' welfare. The research method employed is a literature study with a qualitative approach, analyzing various Islamic literature sources, including the Quran, Hadith, and fiqh books. The results show that although Muzara'ah and Mukhabarah share some similarities, there are significant differences in terms of seed provision, operational cost distribution, and risk bearing. Muzara'ah involves seed provision by the landowner and shared risk, while in Mukhabarah, the cultivator provides the seeds and bears all the risk. This research also reveals differences of opinion among scholars regarding the pillars and conditions of both contracts. In conclusion, both Muzara'ah and Mukhabarah can be effective solutions to increase agricultural productivity and farmers' welfare, with the choice of contract depending on the conditions and agreements between the parties involved.